Artificial stretchable armor for skin-interfaced wearable devices and soft robotics - Choi, Jungil; Han, Seungyong; Baliwag, Miguel; Kim, Bong Hoon; Jang, Hokyung; Kim, Jin Tae; Hong, Insic; Kim, Taewi; Kang, Seong Min; Lee, Kyu Tae; Kang, Daeshik; Rogers, John A. (Extreme Mechanics Letters, 2022)
Animals such as the armadillo and pangolin have natural armor as a mechanical form of protection from predators. Among the several types of armor that exist in nature, structures composed of thin elastomeric substrates with overlapping hard scales can shield underlying soft tissues from physical impacts and localized stresses while maintaining a level of mechanical compliance necessary for natural motions. Here, we design and fabricate a class of artificial armor that derives inspiration from these natural systems. The optimization process involves systematic tests of several design candidates to assess their mechanical stability against different types of mechanical stresses. The resulting platforms provide highly effective protection layers for wearable electronic devices and soft robotic systems with little constraint on their functionality, as demonstrated with representative devices.
Keywords: Elastomeric substrates; Hard scale; Impact stress; Localized stress; Mechanical; Overlapped structure; Soft robotics; Soft tissue; Stretchable armor; Wearable devices; Overlapped structure; Soft robotics; Stretchable armor; Wearable devices